Kajian kinerja ruas jalan dan solusi pengendalian kemacetan pada Ruas Jalan Antang Raya Kota Makassar - Sari, M Arief Anantama; Badaron, Fauziah; Syafey, Ilham (Jurnal Teknik Industri Terintegrasi (JUTIN), 2025)
The Antang Raya road section is an alternative road section as a traffic route in the eastern area to the center of Makassar City, where congestion problems often occur. As a vital road that is frequently used by vehicles in Makassar City, Jalan Antang Raya has very different conditions in the field. Based on the background and problem formulation that will be discussed, the expected objectives of this research are as follows: 1) Analyze the traffic characteristics related to road traffic traffic flow density on the Antang road section, 2) Examining the results of the performance of the Antang Raya road section on the level of service as a form of congestion in the city of Makassar. The research method uses a quantitative method using the 1997 Indonesian Road Capacity Manual. The results obtained are as follows: 1) Vehicle Volume The survey results show that traffic volume on the Jalan Antang Raya section peaks at certain hours, with varying vehicle speeds, 35 .58 km/hour at peak hours reflects significant congestion conditions during peak hours. 2) Road Density and Capacity: The level of traffic density at the survey point reached the highest value of 56.93 pcu/km, which shows that several points have approached or exceeded the ideal road capacity, potentially causing further congestion. 3) Service Level: Based on the analysis, the service level of the Antang Raya road section is in category D, which indicates that traffic conditions are starting to be less than optimal and require attention for improvement traffic management.